Pendampingan Kesehatan Mental Mahasiswa Semester Akhir melalui Konseling Integratif Islam-CBT sebagai Upaya Penguatan Coping - Alan Kusmawati; Nurjannah Nurjannah (Jurnal Pengabdian Masyarakat, 2026)
Academic anxiety and anxiety about the future are common problems experienced by final semester students, causing decreased motivation, academic delays, and mental health disorders. This community service activity aims to provide integrated Islamic-Cognitive Behavioral Therapy (CBT) support to help students manage anxiety adaptively and sustainably. This community service program is implemented in stages, including preparation, core support through individual and limited group counseling, CBT interventions integrated with Islamic values such as ikhtiar (effort), tawakkal (trust), and husnuzan (firmness), dzikir-based relaxation exercises, as well as reflection and evaluation. The results of the activity showed a decrease in anxiety intensity, a change in irrational thinking patterns to more rational and realistic ones, improved emotional regulation, and the emergence of more adaptive academic behavior. Furthermore, participants experienced a strengthening of their spiritual dimension, which served as an internal resource in dealing with academic pressure and uncertainty about the future. Thus, integrative Islamic CBT counseling can be a relevant, contextual, and applicable model of psychospiritual support in efforts to strengthen the mental health of students in higher education settings.